First report of natural infection with trypanosoma cruzi in rhodnius montenegrensis (Hemiptera, Reduviidae, Triatominae) in Western Amazon, Brazil - Bilheiro, Adriana Benatti; Da Rosa, Joaõ Aristeu [UNESP]; De Oliveira, Jader [UNESP]; Belintani, Tiago [UNESP]; Fontes, Gilberto; Medeiros, Jansen Fernandes; Meneguetti, Dionatas Ulises De Oliveira; Camargo, Luís Marcelo Aranha (SAGE Publications, 2018)
Rhodnius montenegrensis was described in 2012. Since then, reports of the occurrence of this species associated with palm trees near households in Rondônia have been published. This study aimed to analyze the natural infection of R. montenegrensis with trypanosomatids in the municipality of Monte Negro, Rondônia, Brazilian western Amazon. Capture of triatomines occurred in Attalea speciosa (babassu) specimens around households. Twelve of the 72 captured triatomines were identified by morphological and morphometric characters, by molecular analysis made using the PCR, DNA sequencing, and phylogenetic analyses. The intestinal content was collected from 60 of these 72 specimens. The positivity for trypanosomatids was confirmed by examining the intestinal content followed by PCR amplification of the cathepsin L-like gene specific for Trypanosoma cruzi (PCR-DTcrCatL) and Trypanosoma rangeli (PCR-DTraCatL). Of the 60 specimens analyzed by microscopy, 22 (36.7%) were positive for trypanosomatids in the intestinal content analysis. Of these 22 specimens of R. montenegrensis, 16 (72.7%) were infected with T. cruzi, 2 (9.1%) were infected with T. rangeli, 2 (9.1%) had mixed infection with T. cruzi and T. rangeli, and 2 were negative (9.1%). These data suggest the need for attention of the health surveillance system of Chagas disease in the State of Rondônia, as this study points out to another potential vector of the disease.
Keywords: Amazon; natural infection; Rhodnius montenegrensis; triatomines; Trypanosoma cruzi; Trypanosoma rangeli